AN ANALYSIS OF TEMPORAL NUMERICAL SUPERIORITY IN THE PAN-AMERICAN JUNIOR MEN’S WATER POLO MATCHES - Guilherme Tucher; Marco Antônio Pardal; Francine Caetano de Andrade Nogueira; Silvio de Cassio Costa Telles (Journal of Physical Education)
ABSTRACT This study compared the frequency, number of goals and attack efficiency in temporal numerical superiority among winning and losing teams and among balanced and unbalanced matches in a junior men’s water polo competition. Another analysed relationship was that between a balanced or unbalanced final score and the efficiency at scoring goals in numerical superiority in the winning teams’ games. A total of 56 matches from the Pan-American Junior Men’s Water Polo championship was analysed. The teams were categorised as losers or winners and the match results were classified as balanced or unbalanced. The chi-squared and Mann-Whitney tests were used for statistical treatment. There is no significant difference in the occurrence of numerical superiority between winners and losers (p = 0.25) despite the winners scoring more goals (p = 0.002) and being more efficient (p < 0.001). There is no significant difference in the occurrence of numerical superiority (p = 0.81) and goals (p = 0.03) in balanced and unbalanced matches. However, there tends to be a higher shot efficiency (p = 0.01) in unbalanced matches. A significant relationship exists (p = 0.04) between the winning teams’ efficiency at scoring goals in a situation of numerical superiority and an unbalanced score.